Blood metabolites, body condition score, body weight and milk yield in relation to resumption of cyclicity in post-partum buffaloes - KAVYA, K M; SHARMA, R K; JEROME, A; PHULIA, S K; BALHARA, A K; SINGH, I (The Indian Journal of Animal Sciences, 2018)
This study was designed to decipher the relationship between blood metabolites [glucose, total protein, urea, cholesterol, beta hydroxyl-butryicacic (BHBA), and insulin-like growth factor-1 (IGF-1) and leptin], body condition score (BCS), body weight (BW) and milk yield with resumption of post-partum cyclicity in buffaloes. Pluriparous buffaloes were screened using transrectal ultrasonography from day 0 to day 90 at 10 days interval and divided into two groups: I (n=7; buffaloes ovulated <30 days of calving) and II (n=7; anestrous buffaloes >90 days post-partum). Blood samples were collected in both groups at day 0, 10, 20 and 30 post-partum (day 0 considered as calving day) with BW, BCS and milk production observations during first month of lactation. In cyclic buffaloes, serum albumin was higher as compared to acyclic group. In addition, leptin, BW, BCS and milk yield differed with time. Significant correlation between BHBA, IGF-1, leptin and albumin in group I was observed. In conclusion, blood metabolites (albumin, BHBA, IGF-1 and leptin) were significantly correlated with each other in cyclic post-partum buffaloes, but not in acyclic group.